The Analysis of Quality Public Services in Samsat Tebing Tinggi Office, North Sumatra Province - Syafruddin Ritonga; Isnaini Isnaini; Akhmad Ferdinand Siagian (Budapest International Research and Critics University, 2021)
This study aims to determine the effect of the Quality Public Services in Samsat Tebing Tinggi Office, North Sumatra Province. This research is a type of qualitative research. The result shows that the factors are the obstacles and advantages of the One-Stop Integrated Service System Efforts to Improve Public Services at the Tebing Tinggi Samsat Office, North Sumatra Province. That the Integrated Service Implementation Guidelines have been carried out optimally. However, in terms of: Facilities, there are still some obstacles, namely not yet available prayer room facilities, special parking spaces and still using public road facilities for cars and for public transportation motorbikes using a makeshift office yard and during the rainy season in December 2020 there was a 50 cm high flood which resulted in activities being stopped for 5 days. The existence of HR (human resources) in the ranks of Samsat, Bank SUMUT and the ranks of the Directorate of Traffic is very cooperative and cooperates with each other in providing services to taxpayers so that the obstacles faced are always mutual help and solid cooperation.